Geographical dynamics of the Japanese animation industry - Seiji Hanzawa (Netcom)
While research on the geography of the animation industry has highlighted the industrial agglomeration and/or the globalization, it has provided only a limited perspective on the dynamics of the geography in the Japanese animation industry, which has recently been experiencing locational decentralization to the domestic regions outside Tokyo. This article explores the recent transformations of this industry following changes in technologies and production processes. It examines the results of the author's research conducted in Japanese animation companies since 2000. The results suggest that, although decentralization has been facilitated by digital innovations in production technologies, it is also linked to the deterioration of the production environment resulting mainly from the characteristics of the industrial agglomeration.